An Experimental Study on Scale Effect in Dynamic Shear Properties of High-Damping Rubber Bearings - Murota, Nobuo; Mori, Takahiro (Frontiers in Built Environment, 2020)
High-damping rubber bearing (HDRB) is one of the most popular devises which is applied for seismic isolation of structure. In order to clarify characteristics of the HDRB, various loading tests of the bearings have been conducted and the data is applied to the practical design of isolation systems. In this study, in order to investigate the scale effect on physical characteristics of HDRB, dynamic loading tests with full-scale, and scaled-model isolators, which has diameter of 1000mm, and 225mm respectively, were conducted. The test protocol covers shear strain dependency, frequency dependency tests, and repeated loading test, and the difference in shear characteristics caused by specimen scale were investigated. Repeated loading test was conducted only with scaled model, and relationship of temperature increase of the specimen and shear characteristics were evaluated. In parallel, finite element analysis (FEA) of the isolator under repeated loading was conducted. After the constitutive model of FEA was identified by the results, the FEA was extrapolated to simulate repeated loading of 1000, 1600mm diameter isolators, which can not be tested realistically by dynamic loading. dynamic loading, and change of properties along increase of number of cycles, and temperature distribution between full-scale and reduced-scale was investigated. Necessity of consideration for scale effect in evaluation of HDRB properties by dynamic testing is discussed.